EFEKTIVITAS LEMBAGA PEMASYARAKATAN DALAM PENANGGULANGAN TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA TAHUN 2015-2018 (STUDI KASUS LEMBAGA PEMASYARAKATAN KLAS IIB PAYAKUMBUH DAN LEMBAGA PEMASYARAKATAN KLAS II A BUKITTINGGI) - Yuserlina, Anny; Khair, Umul (Ensiklopedia Sosial Review, 2019)
The success of the prison development role will have a good impact on inmates, one of which is the convicts have a high level of consciousness so that there will be no repetition of narcotic crime (a Narcotics). There are many repetitions done by ex-convicts so that correctional institutions are less successful in carrying out construction. The effectiveness of correctional institutions in the prevention of drug crimes in Correctional institution Klas IIB Payakumbuh Klas IIA Bukittinggi has not run to the fullest. As for the factors that become a barrier to prevention of the preventive efforts of narcotics criminal acts of the problem of less employees, budgets, facilities and infrastructure, society and cooperation with outside parties are less effective. The author's suggestion to overcome the obstacles is to be more effective in preventing the prevention of narcotic criminal acts, so there should be experts in the field of spikology, religious and technical so that the construction of prisoners can run As expected.